2012
DOI: 10.4049/jimmunol.1101390
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ Type II NKT Cells Mediate ICOS and Programmed Death-1–Dependent Regulation of Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is a chronic autoimmune disease that results from T cell-mediated destruction of pancreatic β cells. CD1d-restricted NKT lymphocytes have the ability to regulate immunity, including autoimmunity. We previously demonstrated that CD1d-restricted type II NKT cells, which carry diverse TCRs, prevented T1D in the NOD mouse model for the human disease. In this study, we show that CD4+ 24αβ type II NKT cells, but not CD4/CD8 double-negative NKT cells, were sufficient to downregulate diabetogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 54 publications
3
41
0
Order By: Relevance
“…Consistent with the role of tolerized DCs, our data clearly show that adoptive transfer of DCs alone from sulfatide-treated animals is able to protect recipients from EAE. We are investigating potential pathways including ERK1/2 signaling (49) or IL-10 secretion (50) or ICOS/PD-1 dependent signaling (51, 52) by which DCs are tolerized following NKT cell subset interactions leading to control of inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the role of tolerized DCs, our data clearly show that adoptive transfer of DCs alone from sulfatide-treated animals is able to protect recipients from EAE. We are investigating potential pathways including ERK1/2 signaling (49) or IL-10 secretion (50) or ICOS/PD-1 dependent signaling (51, 52) by which DCs are tolerized following NKT cell subset interactions leading to control of inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that type II NKT cells from 24αβ transgenic mice can protect NOD mice from disease, dependent on costimulators inducible costimulator (ICOS) and PD1 interactions (45, 46). Besides being a major lipid in the myelin sheath, different species of sulfatide are also present in pancreatic β-cells and could serve as ligands for type II NKT cells during T1D immunopathogenesis (47).…”
Section: Type II Nkt Cells In Different Diseasesmentioning
confidence: 99%
“…A recent study has suggested that the ICOS and PD-1 ligand pathways are required for the regulation of T1D in NOD mice by CD4 + type II NKT cells (33). Sulfatide-mediated type II NKT cell activation can also result in IL-10 secretion and, consequently, inhibition of type I NKT cells and diabetogenic or encephalitogenic CD4 + and CD8 + T cells (13, 27).…”
Section: A Novel Type II Nkt Cell-mediated Immune Regulatory Pathwaymentioning
confidence: 99%